DAIRY PRODUCTIVITY OF COWS OF THE HOLSTEIN BLACK-AND-WHITE CATTLE OF THE KAZAKHSTAN POPULATION - Zhumanov Kanat Zheksembekovich; Baimukanov Aidar Dastanbekuly (Academic Journal of Physical and Chemical Sciences, 2020)
The article deals with the productive parameters of cows of dairy cattle of the Holstein black-andwhite breed in Kazakhstan. The research aimed to determine the level of productivity of the first-calf heifers of the Holstein black-and-white cattle. As an object of the research, information was used on first-calf heifers lactating in 2016-2017 in the breeding herds of the Holstein black-and-white cattle of the Republic of Kazakhstan. The source was the official data of the information-analytical system (IAS) of the livestock breeding of the Republic. The data analysis on the dairy productivity of the cows-daughters of the estimated servicing bulls is carried out according to the indicators of milk yield, the fat and protein content in milk, the yield of milk fat and protein for 305 days of lactation and the research period.